Agri-silvicultural Studies on Raising of Oil, Seeds Like Sesamum indicum Linn. (Til), Arachys hypogea Linn. (Groundnut) and Glycine max Merrill. (Soybean) as Cash Crops in Conjunction with Dalbergia sissoo Roxb. and Tectona Grandis Linn. at Mandar, Ranchi - Mishra, J.; Prasad, U. N. (Indian Forester, 1980)
Agri-silvicultural studies were conducted in the newly felled forest area of Mandar, Ranchi on raising of cash crops in conjunction with sissoo and teak in July, 1978 under rainfed conditions with the main objectives to study the effect on associate cash crops, the method of propagation, effect of fertiliser application on cash crops and main forest species, the economics etc. The observations made and the results obtained during the first year of plantation indicate that soil conservation measures, neutralisation of soil acidity and proper application of N, P&K in place of cow dung manure are probably necessary to grow successful cash crops in Ranchi conditions. Til has shown to be a poor crop but groundnut and soyabean seem to prove highly remunerative. During the first year of plantation, no significant difference was observed in the growth of teak and sisson in control and in combination with cash crops but its effect on soil has heen significant because under all the three types of cash crops, there has heen a gain in N&P in the soil but a litlle decline in K.